Amortecimento de oscilações eletromecânicas em um sistema carga-frequência utilizando Tabu Search - Santos, Camila Jéssica Sampaio dos (2019)
This work presents the design of a robust controller with the main objective of damping electromechanical oscillation modes (MOE) in power systems of three areas, seeking to achieve the robust stability of the system. Techniques for analysis and design of multivariate frequency domain controllers are used to verify the possibility of obtaining robust control with decentralized reduced-order controllers. In order for the controllers to achieve robustness, it is necessary to select the most significant input-output pairs for the system. For this purpose, analysis techniques were applied to a load-frequency system of three areas. The controller is of type H_∞ and the optimization method applied, to obtain the robust control of the system with uncertainties, was the tabu search.